2022
DOI: 10.5194/amt-15-4675-2022
|View full text |Cite
|
Sign up to set email alerts
|

Combined organic and inorganic source apportionment on yearlong ToF-ACSM dataset at a suburban station in Athens

Abstract: Abstract. The current improvements in aerosol mass spectrometers in resolution and sensitivity, and the analytical tools for mass spectra deconvolution, have enabled the in-depth analysis of ambient organic aerosol (OA) properties. Although OA constitutes a major fraction of ambient aerosol, its properties are determined to a great extent by the mixing characteristics of both organic and inorganic components of ambient aerosol. This work applies a new methodology to a year-long ACSM dataset to assess the sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…S2), as well as at early afternoon (15:00-20:00 UTC+2). At the DEM station, the 30 nm particles are primarily related to traffic emissions and to a lesser extent to new particle formation (Vratolis et al, 2019;Zografou et al, 2022). This was also confirmed in the present study by the cluster analysis of the number size distributions.…”
Section: Annual and Seasonal Diurnal Variabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…S2), as well as at early afternoon (15:00-20:00 UTC+2). At the DEM station, the 30 nm particles are primarily related to traffic emissions and to a lesser extent to new particle formation (Vratolis et al, 2019;Zografou et al, 2022). This was also confirmed in the present study by the cluster analysis of the number size distributions.…”
Section: Annual and Seasonal Diurnal Variabilitysupporting
confidence: 89%
“…Particle number size distributions vary across different regions and environments (Rose et al, 2021), and the structure of their patterns can be used as an indicator of the possible aerosol particle emission sources and formation processes. At the DEM station, secondary aerosol formation, mostly related to sulfate and organics (Kostenidou et al, 2015;Tsiflikiotou et al, 2019), and traffic-related emissions are the main sources of ambient aerosol (Zografou et al 2022), while biomass burning also constitutes a major source in winter (Vratolis et al, 2019;Bousiotis et al, 2021). In the present study, five clusters were identified which represent a combination of the major particle emission sources and formation/transformation processes.…”
Section: Cluster Analysis and Aerosol Hygroscopic Propertiesmentioning
confidence: 99%
“…The Approach 1 results already represent an improvement with respect to the OA SA, which led to the identification of five OA sources: HOA, COA, BBOA, LO-OOA and MO-OOA as reported by Via et al (2021). The addition of the inorganic NR-PM 1 and BC species already proved advantageous in Zografou et al (2022) by identifying an additional factor. Similarly, the present SA solution consists of 6 factors, 3 purely primary, 2 secondary and a potentially mixed factor (Figure S4).…”
Section: Independent Pmfmentioning
confidence: 81%
“…Some others performed source apportionment by including both organic and inorganic fractions from the AMS (Äijälä et al, 2019;McGuire et al, 2014;Sun et al, 2012), improving the factors resolution and their chemical nature. More recently, Zografou et al (2022) performed PMF analysis on combined organic and inorganic year-long dataset from a ToF-ACSM. Tong et al (2022) combined into a single dataset AMS and extractive electrospray ionisation time-of-flight mass spectrometer (EESI-ToF) measurements providing an optimised identification and quantification of the organic factors, more specifically the SOA fraction.…”
Section: Introductionmentioning
confidence: 99%